The comparisons on wave breaking captured by non-hydrostatic model with or without turbulent dissipation - Dongbin He; Dongbin He; Yanli He; Yanli He; Yanli He; Hongfei Mao; Hongfei Mao; Junyu Li (Frontiers in Marine Science)
The spilling and plunging breakers in surf zone are simulated by the non-hydrostatic shock-capturing model with or without turbulent dissipation/model. Geometric and dynamic breaking criteria and wave energy flux are investigated to show the differences on breaking onset and energy dissipation. Comparisons between the k-ϵ and laminar data indicate that both of them give reasonable results, but the absence of turbulent dissipation would cause the seaward movement of breaking point, the underestimation of maximum breaking wave height, and the overprediction of breaking energy loss. And the laminar data presents greater change for velocities near the surface and bottom, resulting in a significantly larger proportion of kinetic energy flux after wave breaking, while the k-ϵ data can give better consistency with the measured in velocity calculations.